The Effects of Adverse Childhood Experiences on Internalizing and Externalizing Behaviors among Black Children and Youth - Hicks, Megan R. (J Child Adolesc Trauma, 2020)
There is limited research on the short-term effects of ACEs on Black children and youth. Black children and youth are disproportionately exposed to abuse, neglect, and other victimizations (Drake et al. 2009; Wade et al. Journal of Family Issues, 17(3), 283–316, 2014). Investigating ACEs will provide a broader understanding of childhood trauma on developmental processes. The current study investigates how ACES impacts psychological distress, substance use, and delinquency among Black children and youth. Hypotheses were tested using a subsample of longitudinal data from 265 participants who were recruited from six school districts in Southeast Michigan. ACEs at T1 significantly predicted depressive symptoms at T2 (β = .19, p < .05), which in turn predicted substance use (β = .20, p < .05), and delinquency (β = .19, p < .05). Psychological distress also mediated the associations between ACEs and substance use, and delinquency. To engage youth in prevention/interventions and practice, it is important to understand the contexts in which they develop i.e. having knowledge on the specific type of victimization instances that Black youth may experience more than their peers as well as the social factors. Therefore, taking a trauma-informed approach that will acknowledge the adverse childhood experiences that youth went through and to understand how these experiences shape their development through adolescence may be efficacious.